THE MEAN STELLAR SPECTRA OF COOL GIANT STARS - A. V. Dragunova; S. I. Belik; N. S. Komarov (Odessa Astronomical Publications, 2017)
The mean values of energy distributions in spectra of cool stars of various spectral types have been found using the Catalogue of spectra of 555 stars.